العوامل المؤثرة على نجاح مدارس النساء الريفيات في ولاية الجزيرة، السودان - عمر, مها محمد عثمان; العجب, معتصم علي محمد; الحسين, الشفاء النور يوسف (Gezira Journal of Agricultural Science; Vol 23 No 1 (2025), 2026)
هدفت هذه الدراسة الي معرفة العوامل المؤثرة على نجاح مدارس النساء الريفيات في ولاية الجزيرة. وتشمل متغيرات الدراسة الخصائص الديموغرافية، المشاركة و المنهج كمتغيرات مستقلة وتطبيق المحتوى التدريبي وتغيير السلوك وقبول الاسرة للمعارف والمهارات المكتسبة ودور المدارس في حياة المبحوثات وتبني المشروعات لزيادة الدخل وتحقيق المدارس لأهدافها كمتغيرات تابعة. استخدم المنهج الوصفي، شمل مجتمع الدراسة عدد (2524) دارسة في الفترة من (2016 -2021). استخدمت العينة الطبقية بحجم (400) مبحوثة بنسبة 15.8% من شاملة المبحوثات وذلك باستخدام المعادلة الإحصائية لاختيار العينة. و جمعت البينات باستخدام استمارة استبيان خاصة بالمبحوثات و تم إجراء اختبار أولي (Pre-test)  للتحقق من ثباتها وصلاحيتها. ولتحليل البيانات استخدم برنامج الحزم الإحصائية للعلوم الاجتماعية (SPSS) بالاعتماد على المنهج الوصفي التحليلي و شمل (التكرارات، والنسب المئوية) ومربع كاي لبيان معنوية العلاقات. وقد أوضحت نتائج هذه الدراسة ما يلي: أولا: نتائج التحليل الوصفي لبعض الخصائص الديموغرافية مثل (الحالة الاجتماعية ، التعليم وعدد أفراد الأسرة) إتضح أن 43.5% من المبحوثات كن متزوجات. وأن 28.8% من المبحوثات تعليمهن ثانوي وأن  80.5% من المبحوثات أسرهن صغيرة الحجم تتراوح بين (2-4) افراد. كما اتضح أن 65 % من المبحوثات المواظبات على الحضور للمدرسة.  و أن 73.7% من المبحوثات يشاركن بالنقاش و المعينات أثناء التدريب مما يؤكد حرصهن على الاستفادة من برامج المدارس. و أن 83.3 % من المبحوثات يعتقدن أن حضور زميلاتهن للمدرسة كان جيّدا، مما يؤكد اهمية المدارس بالنسبة للدارسات والرغبة الأكيدة والاهتمام بالمنهج والحرص على الاستفادة منه.  و أن 53.5 % من المبحوثات أوضحن أن المنهج يغطي كافة المجالات بالتركيز على المجالات الاقتصادية ، الصحية ، التعليمية و الزراعية . وأن 79.2 % من المبحوثات ذكرن أن محتوى المنهج المعد مناسب. وفيما يخص محتوى البرامج الزراعية في المنهج التدريبي اتضح أن 68.2 % من المبحوثات ذكرن أن المنهج يركز على الانتاج النباتي ، 52.% منهن فقط ذكرن أن المنهج يغطي الشق الحيواني.  وأن 40% من المبحوثات ذكرن أن كل طرق التدريب استخدمت أثناء تنفيذ برامج المدارس. ثانيا: نتائج تحليل مربع كاي: أوضحت النتائج  أنه توجد علاقة معنوية بين الحالة الاجتماعية للمبحوثات كمتغير مستقل وكل من التغيير الإيجابي في السلوك وقبول الأسرة  للمعارف المكتسبة كمتغيرات تابعة. وأنه توجد علاقة معنوية عالية بين مستوي التعليم للمبحوثات كمتغير مستقل وتطبيق المحتوي التدريبي والتغير الايجابي في السلوك بعد التدريب وقبول الاسرة للمعارف المكتسبة وتطبيقها ودور المدارس في حياة الريفيات وتحقيق المدارس لأهدافها كمتغيرات تابعة. وأنه توجد علاقة معنوية عالية بين عدد أفراد الاسرة كمتغير مستقل وكل من قبول الاسرة للمعارف المكتسبة وتطبيقها وتبني مشروع لزيادة الدخل كمتغيرات تابعة. وأنه  توجد علاقة معنوية عالية بين المشاركة أثناء التدريب كمتغير مستقل وتطبيق المحتوي التدريبي وقبول الأسرة للمعارف المكتسبة ودور المدارس في حياة الريفيات وتبني مشروع لزيادة الدخل كمتغيرات تابعة. وأن هنالك علاقة معنويه عالية بين تغطية المنهج للاحتياجات كمتغير مستقل وكل من التغيير  الايجابي في السلوك و قبول الاسرة للمعارف المكتسبة ودور المدارس وتحقيق المدارس لأهدافها كمتغيرات تابعة. وقد أوصت الدراسة بالآتي: على الجهات الحكومية التوسع في نشر فكرة المدارس وإنشاءها في محليات الولاية المختلفة وعلى المبحوثات الانتظام في الحضور والمشاركة وتطبيق ما تعلمنه وتبني المشاريع المدرة للدخل. وتدعيم المنهج بمقررات إضافية حسب احتياجات ورغبة الدارسات تواكب التغيرات والتكنولوجيا الحديثة وتشجيع النساء بالمساهمة في وضع المنهج الذي يتناسب مع طبيعة المرأة الريفية واحتياجاتهن والتوسع في استخدام طرق ووسائل تعليمية تناسب تعليم المبحوثات في تنفيذ برامج المدارس.  The objective of this study is to detect the factors influencing the success of rural women’s schools in Gezira State. Variables of the study were demographic characteristics, participation and curriculum as independent variables, on the other hand; application of training contents, positive change in behavior, family acceptance of acquired knowledge, the role of schools in the lives of the respondents, adopting projects to increase income and achieving schools’ goals as dependent variables. The study used the descriptive approach. The study population included 51 schools in the Gezira state localities as study area, regarding respondents, it included 2524 female respondents in the period from 2016 - 2021. The study used a stratified random sampling technique, using the statistical equation for sample size, a sample of 400 respondents were selected, representing 15.8% of the total respondents’ (population). For data collection, a questionnaire form for the respondents was used, and a pre-test was conducted to verify its stability and validity.  While for data analysis, Statistical Package for the Social Sciences (SPSS) was used, relying on descriptive analysis (frequencies, percentages) and Chi-square to indicate the significance of relationships. Findings of the study were; Firstly, The results of the descriptive analysis of some demographic characteristics such as (marital status, education, and number of family members) showed that 43.5% of the respondents were married. 28.8% of them had a secondary education, 80.5% of them had small families ranging between  2-4  individuals, 65% of them were regularly attend the school training, 73.7% of them participate in discussions during training sessions, 83.3% of them believed that the classmates’ attendance at school was good, 53.5% of them explained that the curriculum covers all fields, focusing on the economic, health, educational, agricultural fields respectively, 79.2% of them stated that the contents of the prepared curriculum was appropriate. Regarding the contents of agricultural programs 68.2% of them stated that the curriculum focuses on plant production, and only 25% of them stated that the curriculum covers the animal part and 40% of the respondents stated that all training methods were used during the implementation of school programs. Secondly, Results of the chi-square analysis: The results showed that there is a significant relationship between the marital status as an independent variable and the variables (positive change in behavior and the family’s acceptance) as dependent variables. There is a highly significant relationship between educational level as an independent variable, and the variables (application of the training contents, positive change in behavior after training, family’s acceptance, role of schools in the respondents’ lives, and the schools’ achievement of their goals) as dependent variables. There is a high significant relationship between the family members as independent variable and the variables (family’s acceptance, adoption of a projects to increase income) as dependent variables. There is a high significant relationship between participation during training as an independent variable, and variables (application of the training content, family acceptance of acquired knowledge, the role of schools in respondents’ lives, and adoption of a project to increase income) as dependent variables. There is a significant relationship between the curriculum’s coverage of needs as an independent variable, and variables (positive change in behavior, family acceptance of acquired knowledge, the role of schools, and schools’ achievement of their goals) as dependent variables. The study recommends the following: Government should help in dissemination of the idea of ​​schools and establish them in the various localities of the state. The respondents should regularly attend, participate, apply what they have learned, and they have adopt income-generating projects. Strengthening the curriculum with additional courses according to the needs and desires of female students that keep up with changes and modern technology. Encouraging women to contribute to developing a curriculum that suits the nature of rural women and their needs, and expanding the use of educational methods and means that suit the education of female respondents to implement the school programs.